Strategi Pengelolaan Kelas Homogen di SDIT Permata Kota Mojokerto - Mei Kalimatusyaro; Kusnul Munfa’ati; Nabila Mashayati Azmi; Fitria Nur Laila; Mutoharoh; Alvy Nur Dina (IAI Al Khoziny Buduran Sidoarjo, 2023)
In Islamic primary schools, the goal of this study is to characterize the teacher's approach to managing homogeneous classes. In June 2023, this study was done on students at SDIT Permata Mojokerto City. Direct interviews with class teachers were used to collect data for this study, and the results of these interviews were used to supplement the main source's data as well as classroom management observations. Data collection is followed by qualitative analysis on the instrument. The goal of this study is to determine how learning results differ across homogeneous and heterogeneous courses. and can fully utilize the ability of each class, but there are still issues that make it fearful that there will be a gender gap that will cause issues in the future. While this class is both homogeneous and heterogeneous, the school or educational institution already has its own policies about it.